Proactive Measures to Combat a SARS-CoV-2 Transmission Among High Risk Patients and Health Care Workers in an Outpatient Dialysis Facility - Jayandiran Pillai; Pagollang Motloba; Keolebogile Shirley Caroline Motaung; Carole Wallis; Lovelyn Uzoma Ozougwu; Debashis Basu; Debashis Basu (Frontiers Media S.A., 2021)
Background: End-stage-renal-failure (ESRF) patients attending clustered out-patient dialysis are susceptible to SARS-CoV-2 infection. Comorbidities render them vulnerable to severe COVID-19. Although preventative and mitigation strategies are recommended, the effect of these are unknown. A period of "potential-high-infectivity" results if a health-care-worker (HCWs) or a patient becomes infected.Aim: We describe and analyze early, universal SARS-CoV-2 real time reverse transcription polymerase chain reaction (RT-PCR) tests, biomarker monitoring and SARS-CoV-2 preventative strategies, in a single dialysis center, after a positive patient was identified.Methodology: The setting was a single outpatient dialysis center in Johannesburg, South Africa which had already implemented preventative strategies. We describe the management of 57 patients and 11 HCWs, after one of the patients tested positive for SARS-CoV-2. All individuals were subjected to RT-PCR tests and biomarkers (Neutrophil-Lymphocyte Ratio, C-reactive protein, and D-Dimer) within 72 h (initial-tests). Individuals with initial negative RT-PCR and abnormal biomarkers (one or more) were subjected to repeat RT-PCR and biomarkers (retest subgroup) during the second week. Additional stringent measures (awareness of viral transmission, dialysis distancing and screening) were implemented during the period of "potential high infectivity." The patient retest subgroup also underwent clustered dialysis until retest results became available.Results: A second positive-patient was identified as a result of early universal RT-PCR tests. In the two positive-patients, biomarker improvement coincided with RT-PCR negative tests. We identified 13 individuals for retesting. None of these retested individuals tested positive for SARS-CoV-2 and there was no deterioration in median biomarker values between initial and retests. Collectively, none of the negative individuals developed COVID-19 symptoms during the period "potential high infectivity."Conclusion: A SARS-CoV-2 outbreak may necessitate additional proactive steps to counteract spread of infection. This includes early universal RT-PCR testing and creating further awareness of the risk of transmission and modifying preventative strategies. Abnormal biomarkers may be poorly predictive of SARS-CoV-2 infection in ESRF patients due to underlying illnesses. Observing dynamic changes in biomarkers in RT-PCR positive and negative-patients may provide insights into general state of health.